Correction to: Crystal Structure and XANES Study of Defect Perovskite (Y1−xPrx)1+δBa2−δCu3O7−y Compounds Prepared by Solid State Synthesis Method (Electronic Materials Letters, (2019), 15, 3, (377-382), 10.1007/s13391-019-00120-3) - Poom Prayoonphokkharat (2019)
© 2019, The Korean Institute of Metals and Materials. In the original publication of the article, the first author’s third affiliation is published incorrectly.